Analyzing the Interconnection between Agricultural Economic Resilience Social Equity and Environmental Conservation in Sustainable Agribusiness Models - Hartawaty, Dheny Arina (Jurnal Ar Ro'is Mandalika (Armada), 2026)
This research explores the interconnection between agricultural economic resilience, social equity, and environmental conservation in sustainable agribusiness models. It examines how integrating these three factors can improve agricultural sustainability, particularly for smallholder farmers in developing countries, who are often vulnerable to economic shocks, social inequality, and environmental degradation. The study aims to develop a comprehensive framework that combines these elements to create more resilient, inclusive, and sustainable agribusiness models. The research employs a library-based methodology, utilizing secondary data from books, journal articles, case studies, and reports on sustainable agriculture, social equity, and economic resilience. The analysis reveals that integrating economic resilience strategies such as climate-smart agriculture, promoting social equity by ensuring access to resources for marginalized groups, and adopting environmentally sustainable practices significantly improves the productivity and sustainability of agricultural systems. Furthermore, the study highlights the need for policies that foster the interconnectedness of these factors, ensuring the creation of sustainable agribusinesses that benefit both farmers and the environment. The findings emphasize the importance of an integrated approach to achieve long-term sustainability in agriculture, offering valuable insights for policymakers, farmers, and agribusinesses.